Factors affecting online shoeing behaviour among working adult in Kota Samarahan / Siti Nursyamila Guan Abdullah - Abdullah, Siti Nursyamila Guan (2019)
Online shopping is the current trend of shopping among the worldwide consumers including in Kota Samarahan. The convenience and hassle free shopping is the main attraction of online shopping. This study is to investigate the different online factors that give impact towards the online consumers’ behaviour among the working adults who reside in Kota Samarahan.